Determination of the Zn Content in Zincian Malachite by X-ray Diffraction. (12th April 2020) - Jiang, Xin; Ling, Chen; Chen, Xinchao; Chen, Shuaishuai
Abstract: A method for determining Zn content in zincian malachite from a relative location of reflections in an x-ray diffraction (XRD) pattern is reported. Based on the standard samples prepared by a micro-reactor, the (220) reflection of zincian malachite is selected as the reference peak to calculate the relative location of other reflections within the 2 θ -range from 10° to 35°. After establishing the relationship between the Zn content and the relative location, the shifts of these reflections are considered comprehensively to determine the Zn content by multi-peak fitting. The new method takes full advantage of the XRD pattern, avoiding the interference of adjacent reflections in single-peak fitting, eliminating the systematic deviation among different instruments that causes the overall shift of the pattern. Comparing with the Rietveld refinement, the method is more convenient for ordinary user.